Determination of audit delay: The role of board and auditor characteristics - Marsa Riqqah; Dewi Darmastuti (PT WIM Solusi Prima, 2026)
Despite regulations regarding late financial reporting, late submission of financial reports remains a problem in Indonesia, particularly in the cyclical consumer sector, which is sensitive to economic cycles and has a complex supply chain. Furthermore, conditions in this sector are exacerbated by the COVID-19 pandemic, deflation in 2022, and the global economic slowdown in 2023. Policies governing financial reporting deadlines and sanctions are not the primary factors influencing compliance with timely financial report submission. Other factors that may play a role are board characteristics and audit firm characteristics. This study aims to determine the effect of board size, board gender diversity, audit tenure, and audit reputation on audit delay using a population of cyclical consumer sector companies listed on the Indonesia Stock Exchange (IDX) in 2021-2023. Sampling was conducted using a purposive method, resulting in 105 cyclical consumer sector companies listed on the IDX, equivalent to 315 data sets. Using Multiple Linear Regression, the test results indicate that board size has a significant negative effect on audit delay. Meanwhile, board gender diversity, audit tenure, and audit reputation did not significantly influence audit delay. The insignificant board gender diversity is likely due to the very low proportion of women on boards, resulting in small data variations and difficult statistical detection of the effect. Auditor’s characteristics were insignificant, implying that client's internal preparedness appears to be the dominant determinant of audit delay. These findings suggest that companies and regulators should consider board structure and internal process efficiency to minimize audit delay.